Effects of Trichophyton mentagrophytes infection on the immune response of rabbits - Xiao, Chenwen; Bao, Guolian; Wei, Qiang; Liu, Yan; Wang, Jiaoyu; Ji, Quanan; Huang, Yee (PeerJ, 2019)
Background Rabbit breeding has developed into a large-scale industry, and as such, the incidence of dermatophytosis in rabbits has become increasingly common. A rabbit model with Trichophyton mentagrophytes infection was established to study the changes within the immune responses after fungal infection. Methods After the T. mentagrophytes challenge on skin, pathogens on the skin were isolated from the rabbits in the fungal infection (FI) groups 20 days. Fungal observation under microscope were carried out. Identification of strains was achieved by polymerase chain reaction (PCR) using the CDR1 gene. The collected anticoagulant blood samples were analyzed for various blood cell parameters. The levels of antibodies, including IgM and IgA, cytokines, including IL-2, IL-6, and macrophage colony-stimulating factor (M-CSF), and soluble CD4 and CD8 in the serum of the FI group vs. the control group were determined independently. RNA isolation from blood samples and fluorescence-based quantitative PCR were carried out for the mRNA level of M-csf 20 days after fungal challenge. Results Our model resulted in typical symptoms of dermatophytosis on rabbit skin after challenged with fungus. Pathogens isolated from the infected rabbit skin were confirmed to be T. mentagrophytes by microscopic examination and PCR. The number of lymphocytes in the blood of the FI group was significantly decreased in comparison to the control group 2 days after the fungal challenge, but was significantly increased in comparison the control group 10 days after the fungal challenge (P < 0.01). Platelet counts of the FI group were significantly higher than in the control group at 2 (P < 0.05), 10 (P < 0.05), and 20 (P < 0.01) days after fungal challenge. The red blood cell distribution width of the FI group was significantly increased in comparison to that of the control group at 2, 10, and 20 days after fungal challenge (P < 0.01 for all days). The levels of antibodies (immunoglobulin (Ig) M and IgA (P < 0.01)), cytokines (interleukin (IL)-6 (P < 0.01), macrophage colony-stimulating factor (M-CSF) (P < 0.05)), and soluble CD4 (P < 0.01) and CD8 (P < 0.01) in the serum were significantly different between the FI and control groups. Serum M-csf mRNA level of the FI group was significantly higher than the control group 20 days after fungal challenge (P < 0.01). Conclusions This study demonstrates how the immune system responds to infection with T. mentagrophytes and provides potential targets for the prevention and treatment of dermatophytosis.
Keywords: Trichophyton mentagrophytes; Immune response indices; Dermatophytosis; Rabbits